2022
DOI: 10.1021/acsomega.1c07303
|View full text |Cite
|
Sign up to set email alerts
|

Modeling the Binding Free Energy of Large Atmospheric Sulfuric Acid–Ammonia Clusters

Abstract: Sulfuric acid and ammonia are believed to account for a large fraction of new-particle formation in the atmosphere. However, it remains unclear how small clusters grow to larger sizes, eventually ending up as stable aerosol particles. Here we present the largest sulfuric acid–ammonia clusters studied to date using quantum chemical methods by calculating the binding free energies of (SA) n (A) n clusters, with n up to 20. Based on benchmark calculations, we apply the B97-3c//GFN1-xTB level of theory to calcula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
46
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 17 publications
(59 citation statements)
references
References 43 publications
11
46
2
Order By: Relevance
“…We note that the binding free energy value is half of the value previously reported in the study by Engsvang and Elm because we report the binding energy per monomer, while the previously reported value is the binding energy per acid–base dimer.…”
Section: Resultssupporting
confidence: 87%
See 4 more Smart Citations
“…We note that the binding free energy value is half of the value previously reported in the study by Engsvang and Elm because we report the binding energy per monomer, while the previously reported value is the binding energy per acid–base dimer.…”
Section: Resultssupporting
confidence: 87%
“…The change in the trend is believed to be due to changes in the coordination environment inside the cluster, which was also noted in our previous study. 23 At small cluster sizes up to (SA) 6 (AM) 6 all of the molecules are exposed to the exterior, which was also observed by DePalma et al 49 For clusters larger than this we start to observe coordination of molecules in the interior. This same tendency toward coordination of the acid by ammonium was also observed for larger nitric acid− ammonia clusters by Ling et al 50 For the smaller clusters, this is observed to be ammonium which is marked for the (SA) 8 (AM) 8 cluster in Figure 1, but as the cluster grows it instead becomes favorable to coordinate one or more bisulfate ions, which has been marked for the (SA) 13 (AM) 13 cluster in Figure 1.…”
Section: Binding and Addition Free Energies This Study Builds Upon Th...supporting
confidence: 76%
See 3 more Smart Citations